Analisis Perbandingan Subsidi Pemerintah Mendorong Adopsi Kendaraan Listrik: Studi Kasus Lintas Negara - Arniati, Arniati; Mayasari, Mega; Yulianingsih, Siska Ayu; Haloho, Gryson Kirshner; Putra, Daniel Rahmat (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2025)
Various policies are carried out to encourage increased sales of electric vehicles, namely by providing incentives to producers or consumers of electric vehicles. This study aims to determine the effectiveness of various incentive policies enacted in Indonesia to increase the use of electric vehicles. This research uses a descriptive qualitative approach with a comparative analysis method, namely a comparison between Indonesia, Norway, China, Germany and the United States. The findings of this research are the effectiveness in evaluating the extent of Indonesia's progress in achieving net zero emissions by implementing electric vehicle subsidy policies and comparing it with four other countries. Increasing the range of subsidies, facilities and infrastructure and increasing the number of electric vehicle purchases will be directly proportional to reducing emissions towards the national net zero emission target.